Bosnian Literature (reprint) (Libellarium: journal for research in the field of information and related sciences, 2022)
The reprint of Bosnian Literature, bibliography composed by Franciscan Ivan Franjo Jukić (1818-1857) is published in this issue of Libellarium as a supplement to Slavko Harni’s contribution ”Bibliographic work of Ivan Franjo Jukić and the end of cultural history. Bibliographies as a source for the history of books and cultural history”.The text was published in two installments in the first literary journal in Bosnia and Herzegovina, Bosanski prijatelj, started and edited by Jukić, the first part in 1850 and the second in 1851.The original of this reprint is preserved in National and University Library, Zagreb. Keywords:Bosnia; Franciscans; Ivan Franjo Jukić; Bosnian friend; National and University Library Zagreb
Keywords: Bosnia; Franciscans; Ivan Franjo Jukić; Bosnian friend; National and University Library Zagreb